An Attenuated Cytomegalovirus Vaccine with a Deletion of a Viral Chemokine Gene Is Protective against Congenital CMV Transmission in a Guinea Pig Model - Michael P. Leviton; Juan C. Lacayo; K. Yeon Choi; Nelmary Hernandez-Alvarado; Andrew Wey; Mark R. Schleiss (Clinical and Developmental Immunology)
Development of a vaccine against congenital cytomegalovirus (CMV) infection is a public health priority, but CMVs encode immune evasion genes that complicate live virus vaccine design. To resolve this problem, this study employed guanosyl phosphoribosyl transferase (gpt) mutagenesis to generate a recombinant guinea pig CMV (GPCMV) with a knockout of a viral chemokine gene, GPCMV MIP (gp1). MIP deletion virus replicated with wild-type kinetics in cell culture but was attenuated in nonpregnant guinea pigs, demonstrating reduced viremia and reduced inflammation and histopathology (compared to a control virus with an intact GPCMV MIP gene) following footpad inoculation. In spite of attenuation, the vaccine was immunogenic, eliciting antibody responses comparable to those observed in natural infection. To assess its protective potential as a vaccine, either recombinant virus or placebo was used to immunize seronegative female guinea pigs. Dams were challenged in the early 3rd trimester with salivary gland-adapted GPCMV. Immunization protected against DNAemia (1/15 in vaccine group versus 12/13 in the control group, P<0.01). Mean birth weights were significantly higher in pups born to vaccinated dams compared to controls (98.7 g versus 71.2 g, P<0.01). Vaccination reduced pup mortality, from 35/50 (70%) in controls to 8/52 (15%) in the immunization group. Congenital GPCMV infection was also reduced, from 35/50 (70%) in controls to 9/52 (17%) in the vaccine group (P<0.0001). We conclude that deletion of an immune modulation gene can attenuate the pathogenicity of GPCMV while resulting in a viral vaccine that retains immunogenicity and demonstrates efficacy against congenital infection and disease.